Prior Learning Assessment and Recognition: Emergence of a Canadian Community of Scholars - Wihak, Christine (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Prior learning assessment and recognition (PLAR) is the practice of reviewing, evaluating, and acknowledging the information, skills, and understanding that adult learners have gained through experiential or self-directed (informal) learning rather than through formal education (Thomas, 2000). As our current economy and workplaces experience rapid and continuing change, PLAR offers a vital contribution to supporting lifelong and life-wide learning (Evans, 2000). Beyond significant benefits to individual adult learners in terms of confidence-building and enhanced reflective capacity, PLAR’s process translates personal and workplace learning into a portable format, a common coin suitable for public recognition in many different venues. PLAR has hence become an integral feature of lifelong learning policies around the globe and is closely linked with the implementation of national and transnational qualification frameworks (Morrissey et al., 2008). PLAR scholars have a vital role in ensuring that policy and practice in this important field is informed by innovative research. This brief report describes a workshop on scholarly PLAR research, held in Ottawa, Canada on November 6 and 7, 2010 with funding from the Social Sciences and Humanities Research Council (SSHRC).